(untitled) (Italian Journal of Public Health, 2010)
Background: Cigarette smoking, active or passive, is related to adverse perinatal outcomes, increased risk of spontaneous abortions, preterm delivery, low birth weight, malformations, placenta previa, and abruption. It is also known to have adverse effects on the fetus and newborn, as well as affecting breastfeeding. The literature data gave the initial idea to identify some possibly smoking-influenced conditions on perinatal/ neonatal outcome indicators. Patients and Methods: Newborns and their mothers admitted to Gynecology& Obstetric Clinic, Skopje, Macedonia were selected to participate in the study. The patients were divided into 3 groups: the first group consisted of newborns unexposed to tobacco smoke, the second group were newborns born to mothers who smoked more than 20 cigarettes per day, who did not try to quit smoking during the pregnancy, and the third group were newborns born to the mothers who don’t smoke, but were in close contact with other smokers (intensively exposed to the tobacco smoke).Methods used: epidemiological, clinical examinations, biochemical analysis and statistical analysis of the results. Our results clearly demonstrated that maternal smoking had a significant effect (p<0.01) on indictors for perinatal/neonatal outcomes such as: prematurity combined with low birth weight (3,3% vs 12% for the first and second group respectively, and 3,3% vs 9,7% for the first and third group respectively), Apgar scores <6 in the 5-th minute (5,3% vs 13,7% for the first and second group respectively, and 5,3% vs 12,7% for the first and third group respectively), elevated NRBC (2,3% vs 14,7% for the first and second group respectively, and 2,3% vs 12,7% for the first and third group respectively), and for pregnancy outcomes, anemia and premature rupture of the amniotic sac membranes. The following indicators were also significantly affected (p<0.05) by maternal smoking: respiratory distress, cord blood gases, prematurity rate, and for the pregnancy outcome placental abruption and anemia of pregnancy. There was also a statistically significant difference between the results in the unexposed group and both exposed groups. Although smoking and tobacco cannot be considered unique factors influencing the worse perinatal/neonatal outcomes, our study suggests that cigarette smoking is the most frequent, and completely preventable risk factor for adverse neonatal outcomes.